FORMAÇÃO DE PROFESSORES: PRESSUPOSTOS QUE INDICAM NECESSIDADE DE TRANSFORMAÇÃO - Wagner Aparecido Caetano; Arilda Inês Miranda Ribeiro (Universidade do Oeste Paulista, 2015)
The actual situation of schools in Brazil and around the world demonstrates the need for studies that address the challenges faced in overcoming difficulties that contribute to the decline of teaching. One way to overcome the inefficiency of the educational policy is to invest in training and professionalization of the teaching profession. Such road ahead will become possible only through actions that can integrate teacher training scientific specifics, necessary to the profession: teaching theories and practices primarily teacher knowledge. The objective of this paper is to elucidate the teaching community as the problem of combining these two aspects (theory and practice), currently away in teacher training. This research relies on the method exploratory study linked data on the Internet (Pisa), through literature and their idiosyncrasies. That done, it becomes possible to drive to the understanding and possible interventions in the current voltage: universal education and teacher professionalization.